N-(2-Chlorobenzoyl)-4-methylbenzenesulfonamide - Suchetan, P. A. (International Union of Crystallography, 2012)
In the title compound, C(14)H(12)ClNO(3)S, the C=O bond is syn to the Cl substituent in the adjacent benzene ring. The C—S—N—C torsion angle is −80.6 (6)°. The chlorobenzoyl ring is disordered and was refined using a split model [occupancy ratio 0.537 (3):0.463 (3)]. In the crystal, molecules are linked by pairs of N—H⋯O(S) hydrogen bonds, forming inversion dimers.